Patient Satisfaction Measurement by MedRisk Instrument - Guimarães, Élcio Alves; Faria, Mariana Nunes; Lima, Kennedy Rodrigues; Makhoul, Kelly Duarte Lima; Sousa, Lucas Resende; Junior, Paulo Cézar Simamoto; Sousa, Gilmar da Cunha; Neto, Alfredo Júlio Fernandes (Manual Therapy, Posturology & Rehabilitation Journal, 2017)
Background: The importance of evaluating the user’s perspective when dealing with the quality of health services has been a constant and the user’s role as protagonist of this system has a direct impact on improving service. Thus, it is essential to know how users evaluate the care provided to rethink professional practices or intervene in the form of organization of services, to its improvement. Objectives: Assess the degree of patient satisfaction through MedRisk Instrument and identify the item that has the greatest impact on overall satisfaction. Methods/Design: The users of a university clinic of physical therapy, in rheumatology and pediatrics sectors, were asked about their degree of satisfaction, using MedRisk instrument. Results: Forty-six users completed the questionnaire. The 2 global measures means were 4,86 and 4,86 in rheumatology sector; and 4,76 and 4,84 in pediatrics sector. The specific items that had higher level of satisfaction and the highest correlation with overall satisfaction were items 6, 7, 8 and 11. Conclusion: The university physiotherapy clinic was assessed with a high degree of satisfaction to its users and items related to the therapist-patient interaction have more influence on overall satisfaction. Thus demonstrating that the MedRisk instrument is effective, functional and wide applicability.